The potential of herbal extracts to inhibit SARS-CoV-2: a pilot study - Michela Luisa De Pellegrin; Anette Rohrhofer; Philipp Schuster; Barbara Schmidt; Philipp Peterburs; André Gessner (Clinical Phytoscience, 2021)
Abstract Background Herbal medicinal products have a long-standing history of use in the therapy of common respiratory infections. We sought to assess the potential of five validated herbal extracts regarding their ability to restrict SARS-CoV-2 replication in vitro: Bronchipret thyme-ivy (BRO TI), Bronchipret thyme-primrose (BRO TP), Imupret (IMU), Sinupret extract (SINx) and Tonsipret (TOP). Methods Vero cells were incubated with different concentrations of herbal extracts and infected with SARS-CoV-2 for 48 hours. The inhibition of viral replication was assessed by determination of the viral RNA load in the cell culture supernatant using quantitative polymerase chain reaction (qPCR). Results SARS-CoV-2 RNA load was reduced by non-cytotoxic concentrations of BRO-TP (up to approximately 1,000-fold) and, to a lesser extent, IMU and TOP (approximately 10-fold). Conclusions Some herbal extracts showed a promising in vitro effectiveness against SARS-CoV-2, suggesting an antiviral potential of herbal medicinal products. The potential of herbal medicines to restrict SARS-CoV-2 and to treat COVID-19 should be investigated further in a clinical setting.